HUBUNGAN PENGETAHUAN GIZI DAN SIKAP MELALUI MEDIA SOSIAL TERHADAP POLA MAKAN MAHASISWA IKEST MUHAMMADIYAH PALEMBANG - Endrayeni (jurnal kesehatan terapan sains dan teknologi, 2024)
Background: Social Media is online media that supports social interaction. Social media uses web-based technology that turns communication into interactive dialogue. Research objective: To determine the relationship between balanced nutritional knowledge and balanced nutritional attitudes through social media on the eating patterns of Muhammadiyah Palembang Health Sciences and Technology Students. Research Method: This research design uses a Chi-Square approach with quantitative methods. Research Results: The results of statistical tests using the chi square test obtained a value of p=0.006, which means there is a significant relationship between knowledge of balanced nutrition and eating patterns. The results of statistical tests using chi square obtained p=0.005, which means there is a significant relationship between balanced nutritional attitudes and eating patterns. Conclusion: there is a relationship between knowledge of balanced nutrition and attitudes towards students' eating patterns, because the higher a person's knowledge and attitude towards eating, the better their diet.